Efficient blue TADF-type organic afterglow material via boric acid-assisted confinement. Issue 81 (21st September 2022) - Shen, Song; Sun, Yuena; Wang, Donghui; Zhang, Zhen; Shi, Yu-e; Wang, Zhenguang
Abstract : A heat treatment method is developed to produce blue afterglow materials, achieving a photoluminescence quantum yield of 65% and an emission lifetime of 0.18 s (afterglow: >2 s). The afterglow is activated by the confinement effect of boric acid. Abstract : A heat treatment method is developed to produce blue afterglow materials, achieving a photoluminescence quantum yield of 65% and an emission lifetime of 0.18 s (afterglow: >2 s). The afterglow is attributed to TADF of norfloxacin, activated by the confinement effect of boric acid.